Analisa Penetapan Harga Pokok Produksi Kerangka Baja Kapal - Hery Margono (Publikasi Indonesia, 2022)
Since the beginning of the administration, Indonesian President Joko Widodo with the Nawa Cita program has initiated the strengthening of Indonesia's identity as a maritime country. President Joko Widodo also has a vision to restore Indonesia's maritime glory which can be achieved by developing the maritime sector. This study aims to provide an alternative in an effort to control production costs by using a standard costing system in which a standard price is first set to be compared/compared with what actually happened, and the comparison will show whether there is a difference that increases profits or similarly. Otherwise it will reduce profits in a company. And in determining and compiling the Cost of Production. Also the classification of Raw Material Costs. The variable to be explained in this study is to examine a small part of a steel frame production product for a new ship building a TB tug. MITRA UTAMA 01 (Length 120 Feet, Width 32, Height 8 Feet, Capacity 500 KL), ordered by PT. Pelayaran Mangkupalas Utama, The purpose of this research is to meet the needs in the transportation of goods by sea, because Indonesia is a maritime country and if this is fulfilled, the better. In this research, the method that I use is library research, field research, interviews and interviews, observation and documentation and the research technique is qualitative data analysis technique and quantitative data. The results of this study obtained specifications for tug boats or tug boats, the results of which can be determined as the cost of production of the steel frame of the ship. Due to the large number of variables, a new building production product for a ship has different characteristics with cost control. In addition, this is because the product of a ship's production also requires no more than a year to complete a new building project